Tematik dan Saintifik dalam Pembelajaran Anak Usia Dini - Pohan, Nurhikmah (ACIECE, 2019)
Early childhood has six aspects of development, namely the development of religious and moral values, cognitive, language, physical motor, and social emotional. These aspects of development must get optimal stimulation from the surrounding environment. Cognitive, language and literacy development can shape thinking skills and build understanding. All aspects of development must get maximum and optimal stimulation through meaningful learning activities for children that involve parents, teachers, and schools. Based on the stages of development, the tendency to learn kindergarten / RA age children has three characteristics, namely concrete, integrative, hierarchical. Thus, in developing PAUD learning models must pay attention to children's characteristics and competencies to be achieved, interactions in the learning process, tools / media, and assessment. Therefore, based on the explanation of the problem above, the writer is interested in researching the learning process by applying a thematic and scientific learning mode